Neurological Assessment of Developmental Delay - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The etiologic or diagnostic yield of the neurologic examination in 60 children referred to a pediatric neurologist for evaluation of global developmental delay was determined at the Montreal Children's Hospital-McGill University, Quebec, Canada.